Nitrificación En La Estabilización De Residuos Líquidos En Un Reactor Batch Aireado Completamente Mezclado - Pérez, Agustín Leiva; Vera, David W. Moreira; Candell, Joffre A. Andrade; Ortiz, Ana María Aveiga; Salabarría, Julio A. Loureiro (European Scientific Journal, ESJ, 2017)
Organic nitrogen concentration and nitrifying efficiency were related with aerobic reactor operation time, varying from zero up to 50 days and working as a Conventional Activated Sludge System, inoculated with sludge from a trickling filter system, packed with plastic media. The total nitrogen concentration at the beginning was adjusted to 70 mg/dm3 , by means of lysine addition and, and the corresponding to dissolved oxygen stayed at least in 3 mg/dm3 . The maximum nitrification efficiency for converting total nitrogen to nitrate was 86%, and about 30 days, was not significantly increased and the alkalinity (expressed as CaCO3) was reduced from 425 down to 57 mg/dm3 , decreasing about 7,50 mg/dm3 for each mg/dm3 of organic nitrogen converted to nitrate.